The Effect of Twelve Dry-land Resistance Training of Performance in Young Recreational Swimmers of Islamshahr - Jabri, Mansour; Feizi, Samaneh; Piri, Ebrahim (International Journal of Business Management and Entrepreneurship, 2023)
Resistance training is one of the training methods that leads to muscle growth, functional improvement and injury prevention for athletes. The aim of the present study was to investigate the effect of twelve weeks dry-land resistance training improving swimmers records. The Present study was semi-experimental. The implementation of the present study, 60 young swimmers were selected and randomly divided into two training and control groups. The exercise group performed resistance exercises for twelve weeks. Absolute power, relative power, lower limb power and 100m free style record were analyzed. Multivariate analysis of variance (MANCOVA) test was used to compare the pre-test and post-test of two groups. Also, in order to compare the post-test of two groups, the correlated t-test was used. Paired t-test was also used to compare the pre-test and post-test of the training group to obtain the effect of resistance training. All statistical tests were performed in SPSS version 26. The results showed that exercise group that performed resistance exercises with weight s for twelve weeks had a significant increase compared to the control group. Also, the factors of absolute strength, relative strength, lower limb strength and telemetry of limbs had a significant increase. In addition, the athletes in the training group had lower sprint records. Resistance training increases hypertrophy in muscles and increases power in swimers. Possibly, increasing the absolute and relative strength of the lower limb muscles can affect the anaerobic system and improve the swimming record. However, more research is needed on the volume and intensity of swimmers' resistance training.